Burnout and Fear of COVID-19 among Medical Students in Japan : Impact of infection history, gender, and social support - Tomono, Misa; Ando, Shinto; Kamau-Mitchell, Caroline; Ihara, Shiichi; Isobe, Ayana; Kido, Hatsune; Sanji, Shohei; Watanabe, Taisei; Tokuda, Haruka; Itokazu, David; Tokuda, Yasuharu (Journal of Public Health Sciences, 2024)
The COVID-19 pandemic caused significant changes in medical students' lives and study methods, with online learning replacing in-person classes and limited opportunities for clinical practice. However, there are few studies about burnout and fear of COVID-19 among medical students, especially in East Asia, and a need for research investigating the impact of gender, a history of COVID-19 infection, and social support. In March 2022, we conducted a cross-sectional web-based survey of 4th/5th year medical students who completed a clinical clerkship in Japan. Our survey included the Japan Burnout Scale (JBS, range 5-85, comprising of emotional exhaustion, depersonalization and reduced personal accomplishment), fear of COVID-19 scale (range, 1-4), gender, school year, COVID-19 history, household composition, online education use, and financial burden. There were 343 respondents and 42.4% were women. Multivariable adjusted linear regression analyses showed that students with a COVID-19 infection history had significantly higher overall burnout, depersonalization, reduced personal accomplishment, and lower fear of COVID-19. Students with low social support (living alone and greater financial burden) had higher overall burnout, emotional exhaustion, and depersonalization. Gender had no significant effect on burnout (mean JBS among women was 38.6 versus 39.3 among men). Gender significantly predicted fear of COVID-19, with women scoring higher (1.60 versus 1.50). The findings of the present study have implications that medical schools should provide pastoral care for their students according to students’ circumstances, especially those who live alone, have a high financial burden, and/or were infected with COVID-19.